Information literacy in higher education: Overview of initiatives at two Ghanaian Universities - Dadzie, P.S. (African Journal of Library Archives and Information Science, 2009)
The paper examines information literacy (IL) initiatives in two universities in Ghana, namely: the University of Ghana and the University of Cape Coast. IL initiatives such as library literacy, computer and media literacy and communication skills literacy carried out at the two universities for their students are described. Information on the IL activities was obtained from various interviews held with directors, heads of departments or officers in charge of the different programmes. Some challenges in the programmes include the lack of collaboration between departments running IL programmes, the large number of students undertaking the courses, inadequate staff and the cumbersome mode of access to and delivery of the IL programmes. Among the recommendations for improved information literacy programmes include commitment by the university management, improvements in information technology infrastructure, fostering of effective partnerships between the library and the teaching faculty, as well as a review of the curriculum of the library schools to include a new core course in information literacy.
Research Artilce
Keywords: Higher education; Information literacy; Life-long learning; University of Cape Coast; University of Ghana